Implementation of Agency Theory Integrative by Creative Economy Actors - Abdul Wahid Mahsuni (Journal Research of Social Science, Economics, and Management, 2021)
Agency theory centers on two individuals: the owner (principal) and management (agent). Agency theory explains the relationship between the delegation of authority from the principal to the agent. The principal and the agent are seen as rational economic people who are solely motivated to maximize their respective personal interests. This study aims to know the agency theory in running the company entrusted to him, the Sunnah Rasulallah SAW. This study aims to analyze the agency theory model from a conventional perspective to support business actors, wants to produce an integrative-innovative agency theory model (Sunnah Rasulullah SAW) that is measurable related to business people. The analytical method uses in-depth descriptive analysis. The methodology used here is different from the methodology of research in accounting vivacious (mainstream), which emphasizes the use of statistical descriptive with interpretive stance with data analysis used is qualitative nature which in the study of the data used could not be expressed in figures. The results showed that the agency implemented by the Prophet as a representative of integration was quite varied, and this was also carried out by previous prophets. Among their main tasks is to introduce Allah and invite his people to believe in Him. In addition, the prophets and apostles are also tasked with correcting the negative behavior of their people in various aspects of life, including economic behavior. Therefore, in the implementation of this integrative agency, sharia transactions will be more profitable both in the global economy and the creative economy.